Penyuluhan Dan Pelatihan Produksi Makanan Berbasis Tepung Rumput Laut Di Desa Tinangkung Kabupaten Bangkep - Sululing, Wadi; Mutalib, Yanti; Lutfie, Mukhtar (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
This community-based empowerment (PBM) is entitled: Counseling and Training on Seaweed Flour- Based Food Production in Tinangkung Village, Bangkep Regency. This empowerment aims to empower the potential possessed by the seaweed cultivation group in Tinangkung Village, South Tinangkung District, Bangkep Regency. The problems faced by the "Sumber Mulia" seaweed cultivation group are (1) seaweed is only sold dry at very cheap prices so it does not provide more profits, (2) Lack of knowledge and skills in processing seaweed, (3) Lack of equipment partner group due to lack of business capital, (4) Lack of insight and skills in attractive product packaging, (5) Lack of knowledge in product marketing, (6) Lack of business management knowledge. Training will be provided starting from production techniques, product packaging and marketing, as well as business management. The implementation method applied to achieve PBM objectives is a combination of several approaches, namely counseling, training and providing assistance with production equipment. So it is hoped that one of the main outcomes of PBM is a measurable increase in partner empowerment, in this case an increase in the type and quality of products and an increase in income from sales of processed seaweed products, namely seaweed flour, chips and seaweed sticks, in addition to increasing knowledge and skills regarding production processes, product packaging and marketing, as well as business management.